2018
DOI: 10.1152/ajpregu.00459.2017
|View full text |Cite
|
Sign up to set email alerts
|

Oleoylethanolamide modulates glucagon-like peptide-1 receptor agonist signaling and enhances exendin-4-mediated weight loss in obese mice

Abstract: Long-acting glucagon-like peptide-1 (GLP-1) receptor (GLP-1R) agonists (GLP-1RA), such as exendin-4 (Ex4), promote weight loss. On the basis of a newly discovered interaction between GLP-1 and oleoylethanolamide (OEA), we tested whether OEA enhances GLP-1RA-mediated anorectic signaling and weight loss. We analyzed the effect of GLP-1+OEA and Ex4+OEA on canonical GLP-1R signaling and other proteins/pathways that contribute to the hypophagic action of GLP-1RA (AMPK, Akt, mTOR, and glycolysis). We demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 72 publications
(114 reference statements)
0
16
1
Order By: Relevance
“…Moreover, the use of OEA supplements has been approved by the FDA for the treatment of obesity and shows prospective effects ( Brown et al, 2018a ). This is contrary to some previous studies revealing the side effects of OEA, indicating the requirement for more detailed studies ( Nielsen et al, 2004 ; Brown et al, 2018b ). These regulations in general help with the maintenance of a proper level of PPAR-α in the intestine and the homeostasis under its regulation.…”
Section: A Pivotal Regulator Of Metabolismcontrasting
confidence: 99%
“…Moreover, the use of OEA supplements has been approved by the FDA for the treatment of obesity and shows prospective effects ( Brown et al, 2018a ). This is contrary to some previous studies revealing the side effects of OEA, indicating the requirement for more detailed studies ( Nielsen et al, 2004 ; Brown et al, 2018b ). These regulations in general help with the maintenance of a proper level of PPAR-α in the intestine and the homeostasis under its regulation.…”
Section: A Pivotal Regulator Of Metabolismcontrasting
confidence: 99%
“…In detail, OEA activates GPR119 receptor expressed on the L cells and triggers GLP-1 release (4,27,32). In addition, recent evidence suggests that GLP-1(7-36) amide (i.e., active GLP-1) interacts with OEA, creating a complex with increased potency to activate GLP-1R (2,3). Importantly, among the different NAEs tested, OEA is the only one having this activity (3).…”
Section: Discussionmentioning
confidence: 99%
“…To explore this, we used exendin-4 (Ex-4), an agonist of GLP-1R whose potency is unaltered by OEA (2,3). After an overnight fast, we injected WT and Napepld DIEC mice with exendin-4 and precisely monitored HFD consumption over time by using metabolic cages.…”
Section: Napepld Diec Mice Have Submaximal Response To Endogenous Glp-1mentioning
confidence: 99%
“…The mechanism responsible for these effects seems to be associated with the ease with which GLP-1RA can penetrate the blood-brain barrier and with the presence of GLP-1R in certain areas of the brain (highlighting the insula, the amygdala, the putamen, and the orbitofrontal cortex) that are involved in appetite control and ingestion of foods [ 116 , 117 ] and that are more active in obese subjects [ 118 ]. In this sense, studies have shown that the binding of GLP-1RA to GLP-1R in these areas of the brain, along with its subsequent activation, seems to be involved in the suppression of certain metabolic pathways, including brain glycolysis, signaling of protein kinase A (PKA), AMP-activated protein kinase (AMPK), protein kinase B (PKB), and the mechanistic Target of Rapamycin (mTOR), promoting a reduction in caloric intake, which results in weight loss [ 119 ].…”
Section: Glp-1ra: Beyond Its Incretin-mimetic Effectmentioning
confidence: 99%
“…Journal of Diabetes Research its subsequent activation, seems to be involved in the suppression of certain metabolic pathways, including brain glycolysis, signaling of protein kinase A (PKA), AMP-activated protein kinase (AMPK), protein kinase B (PKB), and the mechanistic Target of Rapamycin (mTOR), promoting a reduction in caloric intake, which results in weight loss [119].…”
mentioning
confidence: 99%